Economic benefits of different silvo-pastoral systems in Colombia - Burkart, Stefan; Sandoval, Danny; Flórez, Jesús Fernando; Enciso-Valencia, Karen; Triana Ángel, Natalia (International Center for Tropical Agriculture, 2023)
Improving both quality and availability of cattle feed in the tropics is among the main strategies to increase productivity and reduce the sector’s environmental impacts. Over the last decades, high amounts of research and development funds have been allocated to improve forage germplasm leading to the release of different forage cultivars and hybrids (e.g., Urochloa hybrid cvs. Mulato, Mulato II, Cayman, Cobra). According to agronomic evaluations, those cultivars are superior in terms of forage quality, forage availability, and adaptation to different soil and climatic conditions, and provide numerous environmental benefits – even more so when integrated in silvo-pastoral systems (SPS) with shrub and tree legume species. The success of technology development takes, however, only place when the end-users (cattle producers) efficiently use the technologies. Although there exist only few studies that document the adoption and impacts of SPS, the findings show persistently low adoption levels in the tropics. When it comes to new technologies, land-use and adoption decisions by the cattle producer are mainly based on the profitability promises that the technology can generate. Profitability is a fundamental attribute to incentivize or generate adoption but, in many cases, information is not available to the cattle producer or the extension agent supporting decision-making processes. Profitability is, however, not the only measure since other elements exist that contribute to adoption decision-making, such as cultural, behavioral, or environmental factors. In this sense, the objective of this study is to provide an overview on the economic viability of different SPS setups for the Colombian context. Particularly, two case studies are presented, namely (i) a profitability analysis for establishing a SPS for cattle fattening in the lower tropics (0-1,200 m.a.s.l.) that integrates Urochloa hybrid cv. Cayman with Leucaena diversifolia, and (ii) an economic-environmental evaluation for establishing two SPS (also for cattle fattening), that integrate Leucaena leucocephala with Urochloa brizantha cv. Toledo and Urochloa hybrid cv. Cayman, respectively. In this case, the profitability analysis is complemented with estimates on the monetary values of two ecosystem services provided by the SPS, namely the reduction of methane emissions and microclimatic regulation through the provision of shade. For the first case study, the results indicate that the inclusion of Leucaena diversifolia is financially profitable and substantially improves the associated risk and performance indicators. Profitability indicators, i.e., Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), increase in a range of 15-110%, and the probability of obtaining economic loss decreases from 72 to 0%. The results are directly related to increases in animal productivity (49%) and efficiency resulting from including the tree legume. This shows that Leucaena diversifolia has significant potential to increase both animal production and profitability, which is conducive to the sustainable intensification of beef production in grazing systems. For the second case study, the results show that the implementation of both SPS, significantly improves the profitability indicators NPV, IRR, B/C, and reduces the risk of obtaining loss. However, despite these improvements, only the SPS Toledo arrangement results in a positive NPV and IRR but they are still so low that even this most favorable option is not very attractive. The negative indicators for the SPS with Cayman are largely related to the higher establishment costs when compared to the SPS with Toledo. In both cases, the rather discouraging results might also be related to relatively low daily liveweight gains observed in the evaluation (<240 g). This rather unfavorable investment panorama, however, further changes when the monetary values of both methane emissions reductions and microclimatic regulation are integrated into the profitability analysis. Only by integrating the value of methane emissions reductions, which was estimated at >US$6, >US$24, and >US$28 per cattle, hectare, and year, respectively, the NPV of the SPS with Toledo increases by >700% and the one of the SPS with Cayman turns positive. Likewise, the other indicators further improve for both SPS. Nevertheless, this benefit alone still is not enough to make both SPS an attractive investment alternative as the relatively low IRR show. The estimated savings in CO2eq. emissions of 9% in the SPS, however, are attractive when it comes to climate change mitigation. Particularly, a SPS Toledo or SPS Cayman system of 1,000 animals (which would translate into an area of 250 hectares considering the stocking rate of four animals per hectare) can save 145 tons of CO2eq. When the monetary value of microclimatic regulation is included into the profitability analysis, the panorama changes completely. In fact, both SPS become very attractive investment options, with high NPV of >US$29,000, IRR of >220%, B/C of >2.9, and zero risk of economic loss. The establishment of the evaluated SPS generates roughly 60% shade, which strongly contributes to improving (i) animal welfare, (ii) environmental indicators since water consumption by the animals is lower and biodiversity increases, and (iii) productivity and quality indicators. These SPS thus can contribute to both climate change mitigation through the reduction of methane emissions and adaptation through providing thermal comfort to the animals in increasingly hot environments and by augmenting the availability of feed in critical moments. These two case studies show that investing in SPS can be both financially and environmentally attractive and thus contribute to achieving the Sustainable Development Goals.